An essay on impression management: three randomized experiments with financial analysts - Leite, Rodrigo de Oliveira (2015)
This thesis aims to explore the concept of impression management from the financial analysts’ point of view. Impression management is the definition of the act of an agent manipulating an impression that another person have of this agent, in the context of this thesis it happens when a company make graphics to disclosure financial-accounting information in order to manipulate the market’s perception of their performance. Three types of impression management were analyzed: presentation enhancement (color manipulation), measurement distortion (scale manipulation) and selectivity (the disclosure of positive information only). While presentation enhancement improved only the most impulsive financial analysts’ perception of firm’s performance, the measurement distortion improved the perception of performance for both groups of financial analysts (impulsive and reflective). Finally, selectivity improved the financial analysts’ perception of firm’s performance for both groups (impulsive and reflective), although impulsive financial analysts assigned lower ratings when compared to their reflective peers, on average, to a hypothetical company.